Evaluation at the Day Care School: the bodies' discipline and the children's transgression - Elisandra Girardelli Godoi (Universidade Estadual Paulista Júlio de Mesquita Filho, 2010)
This paper discusses the evaluation practices present in the children's education from 0 to 3 years old. The methodology was developed and experienced through qualitative research conducted in a public day-care center in Campinas and during one year. The resources used to obtain the data were: observations and interviews. The evidentevaluation in that place would compare, label, classify, approving and disapproving the children at the same time. The evaluation was based on constant watching and controlling (observing if the child was o belying or not the given rules), even the children's bodies and behavior as: how they should sit eat, sleep, play and others. At the same time, the data revealed that the children does these rules not accepted a resistance to the assignments that were common and equal to everyone which would educate for the discipline and submission. In that way this the children behavior were not aligned with the adult's proposal.